Single‐center experience with early liver transplantation for acute alcohol‐related hepatitis—Limitations of the SALT score and directions for future study - Ivkovic, Ana; Nisavic, Mladen; Yang, Alexander H.; Punko, Diana; Aaron, Ashley Elizabeth; Keegan, Eileen; Bethea, Emily D.; Yeh, Heidi (Clinical transplantation, 2024)
Alcohol‐related liver disease (ALD) is the leading indication for liver transplantation worldwide. Since Mathurin et al. described their experience in providing early liver transplantation for patients with ALD in 2011, other centers have followed suit with generally favorable survival outcomes. This patient population poses a unique clinical challenge given the expedited nature of the evaluation and the lack of any significant sobriety period prior to transplantation. The SALT (Sustained Alcohol Use Post‐Liver Transplant) score is a standardized psychometric tool increasingly used to help stratify the risk of relapse and guide listing decisions for these challenging clinical situations. In 2018, our center introduced a protocol for early liver transplantation for acute alcohol‐related hepatitis (AAH). In this article, we offer a retrospective review of 26 patients transplanted between May 2018 and May 2021, including at least 1‐year follow‐up, and compare outcomes to initial SALT scores; we further identify additional factors that may impact post‐transplant success. As transplant committees continue to weigh the ethical dilemma of denying lifesaving treatment against the obligation to remain stewards of a limited resource, we aim to contribute to a more nuanced understanding of risk regarding early transplantation for ALD.